2021
DOI: 10.3390/foods10030507
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Grape Pomace Powder on the Phenolic Bioaccessibility and on In Vitro Starch Digestibility of Wheat Based Bread

Abstract: Breads were prepared by substituting common wheat flour with 0 (GP0), 5 (GP5) and 10 (GP10) g/100 g (w/w) of grape pomace powder (GPP) and were analyzed for the phenolic profile bioaccessibility as well as the in vitro starch digestion during simulated digestion. The free and bound phenolic composition of native GPP and resulting breads were profiled using ultra-high-performance chromatography-quadrupole-time-of-flight (UHPLC-QTOF). The raw GPP was characterized by 190 polyphenols with the anthocyanins represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Free and bound phenolics were extracted following the protocol previously reported by Rocchetti et al . (2021). For free phenolics, a homogeniser‐assisted extraction was used (Rocchetti et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Free and bound phenolics were extracted following the protocol previously reported by Rocchetti et al . (2021). For free phenolics, a homogeniser‐assisted extraction was used (Rocchetti et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Different authors evaluated the effect on technological, nutritional and sensory properties of cereal‐based foods fortified with powdered grape pomace (GPP) (Tolve et al ., 2020, 2021), and Rocchetti et al . (2021) investigated the effect of GPP on the phenolic bio‐accessibility of fortified wheat bread, showing an increase of anthocyanins bio‐accessibility and a reduction in the predicted glycaemic index of GPP‐enriched breads. Little information is however available on cereal‐based food fortification with distilled GP (DGP), which represents the by‐product from ethanol extraction.…”
Section: Introductionmentioning
confidence: 99%
“…This approach allowed the advanced characterization of grape pomace but more than that, the fortified bread samples profiling revealed the anthocyanins variation in relation to the bioaccessibility, starch hydrolysis and glycemic index. Moreover, according to the authors, these findings showed that grape pomace enriched bread could promote an antioxidant environment in the digestive tract [78]. In the same regard, Taglieri et al [79] showed that secondary metabolites from Vitellote potatoes significantly improved the phenolic content and antioxidant activity of fortified bread with the highest values when sourdough was the leavening agent.…”
Section: Metabolite Profiling During Wheat Dough Fermentationmentioning
confidence: 94%
“…Another trouble found is the reduction of the digestibility when grape pomace is added to the ruminant diet [8], increasing the environmental impact by elevating the nitrogen requirements [9]. Nevertheless, grape pomace is a promising source of bioactive compounds [5] such as polyphenols, which have been reported to remain up to 70% in grape pomace [10]. Polyphenols are known to present not only cardio-protective, anti-inflammatory, antidiabetic, antimicrobial, among other biological activities, but also excellent properties as food preservatives due their antioxidant and antibacterial capacity [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%